1990
DOI: 10.1111/j.1476-5381.1990.tb14165.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbachol and (−)‐N6‐phenylisopropyladenosine on myocardial inositol phosphate content and force of contraction

Abstract: 1 The effects of carbachol and the A1-adenosine receptor agonist (-)-N6-phenylisopropyladenosine (PIA) on force of contraction and inositol lipid metabolism were studied in electrically driven left auricles and papillary muscles isolated from guinea-pig hearts. Both carbachol and PIA (0.01-10/iM) had concentration-dependent negative inotropic effects in auricles. In papillary muscles PIA had no inotropic effect. Carbachol also had no inotropic effect at low concentrations (0.01-1 pM) but at 10-1OOpM it exerted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Activation of the A 1 R by the agonist R-(Ϫ)N 6 -(2-phenylisopropyl)-adenosine (PIA) has been reported to elevate inositol triphosphate levels in the myocardium (23). Others have reported, in avian ventricular myocytes, that the A 1 R agonist CCPA induces the accumulation of 1,2-diacylglycerol (DAG) and inositol phosphates, suggesting that the A 1 R is coupled to phospholipase C (PLC) (34).…”
mentioning
confidence: 98%
“…Activation of the A 1 R by the agonist R-(Ϫ)N 6 -(2-phenylisopropyl)-adenosine (PIA) has been reported to elevate inositol triphosphate levels in the myocardium (23). Others have reported, in avian ventricular myocytes, that the A 1 R agonist CCPA induces the accumulation of 1,2-diacylglycerol (DAG) and inositol phosphates, suggesting that the A 1 R is coupled to phospholipase C (PLC) (34).…”
mentioning
confidence: 98%
“…In cardiac myocytes, the activation of several types of receptors, such as ␣ 1 -adrenergic (1)(2)(3)(4)(5), muscarinic (1,6), and purinergic (6) dynorphin A (7), endothelin-1 (8,9), and angiotensin II (10 -12) receptors, stimulates the hydrolysis of membrane phosphoinositides leading to the generation of two classes of second messengers, diacylglycerol and inositol trisphosphate. In many tissues diacylglycerol directly activates both the conventional Ca 2ϩ -dependent group of PKC 1 isozymes (␣, ␤ I , ␤ II , and ␥) and the novel Ca 2ϩ -independent group of PKC isozymes (␦, ⑀, , and ), whereas inositol trisphosphate, by increasing intracellular Ca 2ϩ , indirectly activates Ca 2ϩ -dependent PKC isozymes (for a review, see Ref.…”
Section: Sensitivity Respectively Of Actomyosin S-1 Mgatpasementioning
confidence: 99%
“…Adenosine is reported to increase the content of inositol 1,4,5-trisphosphate through increases in diacylglycerol (24), suggesting that protein kinase C may deactivate ectosolic and cytosolic 5 '-nucleotidase. However, we have preliminarily reported that protein kinase C rather activates 5 '-nucleotidase in rat cardiomyocytes (25 5 '-nucleotidase is not the sole determinant of adenosine release.…”
Section: Resultsmentioning
confidence: 99%